Editorial e expediente - Fatorelli, Antonio; Travancas, Isabel; Murari, Lucas (Revista Eco-Pós, 2024)
Revista Eco-Pós, v. 27, n. 2, 2024 Antonio Fatorelli, Isabel Travancas, Lucas Murari Com a colaboração da equipe da Revista Eco-Pós